The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fgene.2022.1000667
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk scores: An overview from bench to bedside for personalised medicine

Abstract: Since the first polygenic risk score (PRS) in 2007, research in this area has progressed significantly. The increasing number of SNPs that have been identified by large scale GWAS analyses has fuelled the development of a myriad of PRSs for a wide variety of diseases and, more recently, to PRSs that potentially identify differential response to specific drugs. PRSs constitute a composite genomic biomarker and potential applications for PRSs in clinical practice encompass risk prediction and disease screening, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 167 publications
0
13
0
Order By: Relevance
“…Combined, these six variants explained only 3.5% of the variation in platelet function. Regarding warfarin, studies utilizing PRS based on variations in CYP2C9 , VKORC1 and CYP4F2 suggested improved dosing through pharmacogenomic algorithms compared to clinical algorithms and fixed dosing regimens [70]. Additionally, a high PRS for coronary artery disease was associated with an increased risk of recurrent MACE after acute coronary syndrome and exhibited a greater absolute and relative risk reduction with alirocumab treatment [71].…”
Section: Prs In Cardiovascular Diseases and Their Treatmentmentioning
confidence: 99%
“…Combined, these six variants explained only 3.5% of the variation in platelet function. Regarding warfarin, studies utilizing PRS based on variations in CYP2C9 , VKORC1 and CYP4F2 suggested improved dosing through pharmacogenomic algorithms compared to clinical algorithms and fixed dosing regimens [70]. Additionally, a high PRS for coronary artery disease was associated with an increased risk of recurrent MACE after acute coronary syndrome and exhibited a greater absolute and relative risk reduction with alirocumab treatment [71].…”
Section: Prs In Cardiovascular Diseases and Their Treatmentmentioning
confidence: 99%
“…Many complex traits, including both responses to drugs and susceptibility to adverse drug reactions, are likely to involve contributions from a number of different genetic variants [ 46 , 47 ]. As a result of the considerable progress made in studies involving genome-wide association studies and genome sequencing, a number of polygenic risk scores based on a number of genetic variants have been developed, but very few of these relate to pharmacogenomics [ 47 ]. Though a very promising approach, implementation in routine clinical practice to date is limited.…”
Section: Polygenic Risk Scoresmentioning
confidence: 99%
“…p-value thresholds, clumping, Bayesian or lasso-based penalization), packages (eg PRScs, LDpred2) and assessment applied can largely affect the end product which may be ultimately differentiated across studies. It is therefore highlighted that standardization of the PRS extraction process 49 is central to facilitating their validation and sequentially increasing their predictive ability. Additionally, in this context, attempts to practically compare PRS results and methodology 4,50-52 can provide useful data for the next steps in the need for a unified, applicable approach to allow for PRSs capable of yielding rapid but reliable results and effective comparisons of findings between populations of different characteristics.…”
Section: Challenges In Prs Construction and Interpretationmentioning
confidence: 99%
“…Although there is a limited number of studies investigating and discussing the extent of PRS effective translation to date, future directions can be encouraging on the incorporation of PRS methodologies in the daily practice [1][2][3] . PRS inclusion in disease screening and the formation of personalized recommendations could potentially offer a solution to the growing pressure applied to healthcare systems for more inclusive strategies and efficient use of financial resources 49 . In the field of nutrigenetics (i.e.…”
Section: Prs and Nutrigenetics/nutrigenomics In Future Healthcare Pra...mentioning
confidence: 99%
See 1 more Smart Citation